Prokaryotic and viral community structure in the singular chaotropic salt lake Salar de Uyuni. (15th February 2019) - Ramos‐Barbero, María Dolores; Martínez, José M.; Almansa, Cristina; Rodríguez, Nuria; Villamor, Judith; Gomariz, María; Escudero, Cristina; Rubin, Sergio dC; Antón, Josefa; Martínez‐García, Manuel; Amils, Ricardo
Summary: Salar de Uyuni (SdU) is the largest hypersaline salt flat and the highest lithium reservoir on Earth. In addition to extreme temperatures and high UV irradiance, SdU has high concentrations of chaotropic salts which can be important factors in controlling microbial diversity. Here, for the first time we characterize the viral diversity of this hypersaline environment during the two seasons, as well as the physicochemical characteristics and the prokaryotic communities of the analysed samples. Most of the selected samples showed a peculiar physicochemical composition and prokaryotic diversity, mostly different from each other even for samples from locations in close proximity or the same season. In contrast to most hypersaline systems Bacteria frequently outnumbered Archaea. Furthermore, an outstanding percentage of members of Salinibacte r sp., likely a species different from the cosmopolitan Salinibacter ruber, was obtained in most of the samples. Viral communities displayed the morphologies normally found in hypersaline environments. Two seasonal samples were chosen for a detailed metagenomic analysis of the viral assemblage. Both viral communities shared common sequences but were dominated by sample‐specific viruses, mirroring the differences also observed in physicochemical and prokaryotic community composition. These metaviromes were distinct from those detected in other hypersaline systems analysed to date.